2014
DOI: 10.1007/s11255-014-0779-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous positive airway pressure on serum cystatin C among obstructive sleep apnea syndrome patients

Abstract: CPAP can decrease cystatin C levels among severe OSA patients and may prevent the latent renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The relationship between sleep apnea and kidney impair/disease is confirmed by several previous studies [35, 1720]. A population-based cohort study in Taiwan demonstrated that patients with sleep apnea had a 1.94-fold and 2.2-fold increase in the incidences of chronic kidney disease and end-stage renal disease [18].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The relationship between sleep apnea and kidney impair/disease is confirmed by several previous studies [35, 1720]. A population-based cohort study in Taiwan demonstrated that patients with sleep apnea had a 1.94-fold and 2.2-fold increase in the incidences of chronic kidney disease and end-stage renal disease [18].…”
Section: Discussionsupporting
confidence: 63%
“…Accumulated data confirmed the bidirectional association between kidney diseases and OSA; for one thing, the incidence and mortality of OSA in kidney disease are higher than those in general population; for the other, OSA contributes the impairs of renal function [2, 3]. Our previous studies indicated that cystatin C, a biomarker of early renal impairs, was higher in several OSA patients without complications [4], and continuous positive airway pressure (CPAP) treatment can normalize cystatin C levels in those patients [5]. The potential mechanisms of OSA-related renal impair are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in another study that included hypertensive patients with OSAS, age (OR = 1.996, 95% CI = 1.366–2.917), blood pressure control (OR = 2.895, 95% CI = 1.267–6.615), and severe OSAS (OR = 6.093, 95% CI = 1.267–29.303) were the influencing factors for Cyst C plasma levels [34]. In the study of Zhang et al [35], 3 months of CPAP treatment significantly reduced Cyst C serum levels in patients with severe OSAS (0.87 ± 0.18 versus 0.77 ± 0.21 mg/L, p = 0.000), but creatinine levels and eGFR were not affected. In another study that included fifty patients with chronic heart failure and sleep disordered breathing, adaptive servoventilation (ASV) significantly improved AHI, central apnea index, obstructive apnea index, arousal index, and mean and lowest hemoglobin saturation compared to baseline and reduced NT-proBNP and Cyst C plasma levels (1.391 ± 0.550 at baseline versus 1.348 ± 0.489 mg/L after ASV, p < 0.05 for Cyst C) [36].…”
Section: Discussionmentioning
confidence: 99%
“…2,53,84,85 Small studies of short duration suggested potential beneficial effects of CPAP on albuminuria and renal function. [86][87][88][89] In patients with T2D, a cross-sectional study of Japanese patients, Oxygen desaturation Index (ODI) ⩾5 was independently associated with microalbuminuria in women but not in men after adjustment for confounders. 90 In another cross-sectional study from the United Kingdom, OSA was associated with CKD in patients with T2D (adjusted OR, 2.64; 95% CI: 1.13-6.16; p = 0.02).…”
Section: Osa and Diabetes Ckdmentioning
confidence: 99%